Personality traits empower entrepreneurial intention of generation Z in Sri Lanka - Mano Weligodapola; Ranitha Sachinthana Weerarathna; Kariyawasam Godage Kavindya Hansini; Pallimulle Hewa Geeganage Wathma Ravini; Wijendra Gamladdalage Tharindu Priyashan Sarathchandra; Samarathunga Muhandiramge Dona Piumi Dilshara Samarathunga (Journal of Innovation and Entrepreneurship, 2023)
Entrepreneurship has a critical role in making society more creative and conscience. Entrepreneurial Intention (EI) guided and supported to build job creators, innovations, and entrepreneurial mindset to foster both men and women entrepreneurial spirit. Youth generation also plays a significant role in economic growth of country. The research predominantly aimed to identify and measure the influence of personality traits on the EI of generation Z in Sri Lanka. The primary cause for concern is the rising demand for entrepreneurs who can spur economic growth by developing fresh concepts and turning them into successful ventures. The present study investigates the impact of the big five personality traits on EI. The study used both quantitative and qualitative approaches. In the qualitative survey, the data collected from eight semi-structured interviews were analyzed using the thematic analysis and NVivo tool. The quantitative survey used a cluster sample of generation Z in the Colombo district, Sri Lanka. A total of 384 valid questionnaires were received and examined. To test the hypotheses, the researchers used Smart PLS software (version 4.0) and the Structure Equation Model technique. The result showed that Conscientiousness, and Neuroticism significantly impact on the EI of generation Z. Further, Extraversion, Agreeableness and Openness to Experience have an insignificant impact on EI. The study gives policymakers and the government advice on how to understand the characteristics of generation Z, which are likely to become future entrepreneurs, and how to support new businesses by providing various incentives.
Keywords: 650; Entrepreneurial Intention; Entrepreneurship; Generation Z; Personality traits